(3GdfHV ddeJYdejfs - (3LGdjfhSs ((3Ydi YeQGf GdMfai GdeJWHH s)
(3ChdgG (B:s
(3Efi PGcQdc CjgG GdMHjH WhKQS ai cJGHi gPG eGjfJaY HeYQaJg GdeJYdehf ef CeQ GdfHV ,hCeG LejY Yde GdfHV abO cJHJg ai cJGH ZjQ gPG aCbhd Gf GdYQhb GdVhGQH cdgG s
(3BNQgG (B:s
(3hQHeG CMS ajg JeOOkG jSjQkG ef GdYQb Je cJGH LGdjfhS ai GdfHV s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GdfSNI HgG MhGTs
(3GfXQ Qbe (B264 (3ef agQS GdWHs
(3HYfhGf GdJHV GdUZjQs
(3bhHdJ HCUdjf SfI (B692(3g`s
(3hHgGeTgG JUMjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs